Konsep Homeschooling Dalam Perspektif Pendidikan Islam - Hairus Sodiq (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
Homeschooling is essentially a directed educational process carried out by parents or families of their children with a conducive teaching and learning process. Either by using a single type of homeschooling, compound homeschooling, and community homeschooling. In Islam, the learning process of the homeschooling model carried out by parents or family is common. In fact, Islam very firmly gives the responsibility of Islamic education to parents. Parents are first and foremost giving education to their children in a good direction so that they are guided into children who can be proud of in the future before God